Exploring The Impact of Digital Financial Literacy on Financial Decisions Among Yogyakarta Millennials - Wilhelmus Taek; Ratih Kusumawardhani; Johannes Maysan Damanik (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study investigates the influence of education, age, and income on the digital financial literacy of millennials residing in Yogyakarta, as well as the relationship between digital financial literacy and financial behaviors such as shopping, and investing. Employing a quantitative research approach, data were collected through a survey of 150 millennial respondents. The findings indicate that socioeconomic factors namely age, education, and income do not significantly impact digital financial literacy. However, the results highlight a strong association between digital financial literacy and millennials' financial behaviors, with substantial influence observed on shopping, and investment decisions. These findings suggest that while socioeconomic characteristics play a limited role in determining digital financial literacy, such literacy remains essential in guiding millennials' financial choices. Ultimately, this study emphasizes the critical role of digital financial literacy in shaping financial behavior, irrespective of the socioeconomic background of millennials.